Operating Short-Term to Long-Term through the COVID-19 Pandemic: Negotiating a Global Renaissance with Science Diplomacy - Berkman, Paul (Tufts Archival Research Center, 2020)
We have lived in a globally-interconnected civilization since World War II, but are still in our infancy to operate on a planetary scale. We now are in the early stages of the COVID-19 pandemic, when common interests in survival are being expressed across the Earth in the absence of global conflict. How can we transform our world at local-global levels, evolving beyond this period of nationalism? How can we respond with informed decisions that couple local-global governance mechanisms and build infrastructure, short-term to long-term? Defying conventional wisdom, the United States and the Soviet Union cooperated continuously in Antarctica and Outer Space throughout the Cold War, despite the animosities that isolated them in every other sphere. The lessons from Antarctica — particularly applying science as a tool of diplomacy — reveal that the starting point of negotiations determines the end result. In Antarctica, the United States and the Soviet Union started from a point of common interests. This presentation will introduce science diplomacy as an international, interdisciplinary, and inclusive (holistic) process, involving informed decision making to balance national interests and common interests for the benefit of all on Earth across generations. Skills, methods, and theory of informed decision making will be discussed with common-interest building as an essential negotiation strategy, triangulating education, research and leadership with science diplomacy as a language of hope.; https://www.pon.harvard.edu/events/negotiating-a-global-renaissance-with-science-diplomacy/; https://www.pon.harvard.edu/daily/teaching-negotiation-daily/operating-short-term-to-long-term-through-the-covid-19-pandemic/